2004
DOI: 10.1073/pnas.0402053101
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in skeletal muscles of caveolin-3-null mice

Abstract: Type 2 diabetes is preceded by the development of insulin resistance, in which the action of insulin is impaired, largely in skeletal muscles. Caveolin-3 (Cav3) is a muscle-specific subtype of caveolin, an example of a scaffolding protein found within membranes. Cav is also known as growth signal inhibitor, although it was recently demonstrated that the genetic disruption of Cav3 did not augment growth in mice. We found, however, that the lack of Cav3 led to the development of insulin resistance, as exemplifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 40 publications
2
86
1
Order By: Relevance
“…This suggests that cholesterol depletion and, presumably, consequent caveolar dysfunction would lead to insulin resistance. Consistently, it was recently reported that caveolin-1 Ϫ/Ϫ and caveolin-3 Ϫ/Ϫ mice, both known to have a dramatic reduction in caveolae, exhibit insulin resistance (38,39). Moreover, in adipocytes treated with TNF-␣, the IR accumulated less in the detergent-insoluble low-density membrane fractions (microdomains) and shifted to the high-density fractions, suggesting a translocation of IR from caveolar to noncaveolar fractions (40).…”
Section: Discussionmentioning
confidence: 57%
“…This suggests that cholesterol depletion and, presumably, consequent caveolar dysfunction would lead to insulin resistance. Consistently, it was recently reported that caveolin-1 Ϫ/Ϫ and caveolin-3 Ϫ/Ϫ mice, both known to have a dramatic reduction in caveolae, exhibit insulin resistance (38,39). Moreover, in adipocytes treated with TNF-␣, the IR accumulated less in the detergent-insoluble low-density membrane fractions (microdomains) and shifted to the high-density fractions, suggesting a translocation of IR from caveolar to noncaveolar fractions (40).…”
Section: Discussionmentioning
confidence: 57%
“…In skeletal muscle, the protein expression of IR and other molecules involved in insulin signalling are unaltered, whereas phosphorylation of IR, IRS or Akt/PKB are all attenuated and insulin-stimulated glucose uptake is decreased [8].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is considerable evidence of caveolin involvement in the modulation of insulin signalling and therefore in the regulation of the intermediary metabolism, which becomes altered in obesity, and associated with metabolic disorders such as insulin resistance and type 2 diabetes [7]. For instance, Cav-3 deficient mice develop late-onset obesity accompanied by insulin resistance in key peripheral tissues and abnormal lipid metabolism [8,9]. Therefore, it is clear that caveolins may play an important regulatory role in muscle insulin signalling.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CAV3 deficiency due to mutations in the gene causes the degeneration of myofibrils, leading to skeletal muscle diseases (Gazzerro et al 2010). Results of functional analyses of CAV3-null mice indicated that CAV3 is an enhancer of insulin signaling (Oshikawa et al 2004). In addition, CAV3 inhibits myostatin signaling through its interaction with ALK5, resulting in increased myofiber size (Ohsawa et al 2004).…”
Section: Discussionmentioning
confidence: 99%